2011
DOI: 10.1021/ja202555m
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Dichlorination of Allylic Alcohols

Abstract: The development of an enantioselective allylic alcohol dichlorination catalyzed by dimeric cinchona alkaloid derivatives and employing aryl iododichlorides as chlorine sources is reported. Reaction optimization, exploration of the substrate scope, and a model for stereoinduction are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
120
0
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(130 citation statements)
references
References 37 publications
1
120
0
9
Order By: Relevance
“…Importantly, the absence of chloriranium ion intermediates can circumvent the site selectivity issue inherent in the nucleophilic trapping of such species with chloride ion: a recognised, and as yet unsolved, problem in controlling the enantioselectivity of dichlorinations of electronically-unbiased, ( E )- or ( Z )-configured alkenes. 15 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the absence of chloriranium ion intermediates can circumvent the site selectivity issue inherent in the nucleophilic trapping of such species with chloride ion: a recognised, and as yet unsolved, problem in controlling the enantioselectivity of dichlorinations of electronically-unbiased, ( E )- or ( Z )-configured alkenes. 15 …”
Section: Discussionmentioning
confidence: 99%
“…The daunting synthetic challenge of constructing such densely functionalized arrays of chlorinated stereogenic centers has provided impetus for the study of (external) diastereocontrol in the dichlorination of chiral alkene substrates, 12 as well as more recent efforts to effect enantioselective dichlorinations of allylic alcohols. 15 …”
mentioning
confidence: 99%
“…12 In contrast, Burns et al have proposed a rather different role for the Lewis base (pre)catalyst (i.e., diol 12 ) in their enantioselective alkene dibromination protocol, suggesting that it may serve to accelerate the nucleophilic trapping of the bromiranium ion intermediate with (Ti-bound) bromide ion, rather than the formation of the bromiranium ion itself (Scheme 5). 15 If this were true, it would constitute “nucleophile activation” as opposed to “electrophile activation” (as depicted in Scheme 6), which is another well-recognized facet of Lewis base catalysis.…”
Section: Challenges For Stereoselective Catalysismentioning
confidence: 99%
“…A number of ( E )-configured, 3-aryl 2-propenyl alcohols are dichlorinated in moderate to good er (71.5:28.5 to 90.5:9.5 er), although O -protected, ( Z )-configured, or aliphatic allylic alcohols are generally less selective (<52.5:47.5 to 81:19 er) (Scheme 4). 12 …”
Section: Introduction: State Of the Artmentioning
confidence: 99%
“…Ring opening of intermediate 16b with chloride ion at the reactive benzylic position would complete the double inversion and account for the experimentally observed stereochemistry. Nicolaou has demonstrated catalytic asymmetric addition of chlorine to allylic alcohols, where regioselectivity of chloronium ion ring opening is a prerequisite for good ee values 29 and Denmark has recently demonstrated that chiral chloronium ions, containing alkyl groups, are configurationally stable. 30 The generality of this novel dichlorination reaction remains to be fully evaluated, but it is significant that it failed with two (11a and 11c) out of three bicyclic substrates.…”
Section: Resultsmentioning
confidence: 99%